2012
DOI: 10.1007/978-3-642-30726-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Polypharmacotherapy in the Elderly: A Clinical Challenge

Abstract: Polypharmacotherapy is a major concern in the elderly and especially in older women after the age of 80. It results from the intake of prescription and non-prescription drugs, being often a problem of evidence-based therapy. Besides the fact that women live longer than men and outnumber them, reasons for polypharmacy in women are diverse and include a different attitude towards intake of drugs between men and women, the propensity of women to rather see a physician and talk about their problems, the load of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
0
21
0
3
Order By: Relevance
“…Dünyada yapılan çalışmalarda polifarmasi ve PID kadınlarda daha yaygın olarak bildirilmiştir. 27,28 Kutsal ve ark.nın çalışmalarında polifarmasi, kadınlarda anlamlı olarak yüksek oranda bildirilmiştir. 20 Ancak bu çalışmada bildirilen kadın katılımcı sayısı, erkek sayısının iki katından fazladır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dünyada yapılan çalışmalarda polifarmasi ve PID kadınlarda daha yaygın olarak bildirilmiştir. 27,28 Kutsal ve ark.nın çalışmalarında polifarmasi, kadınlarda anlamlı olarak yüksek oranda bildirilmiştir. 20 Ancak bu çalışmada bildirilen kadın katılımcı sayısı, erkek sayısının iki katından fazladır.…”
Section: Discussionunclassified
“…28 Çalışma grubunda 80 yaş üzerinde polifarmasi oranının anlamlı olarak arttığı görülmüştür. Bu bulgu, ileri yaşta komorbidite ve hekim başvuru sıklığının polifarmasiye yol açtığı teziyle örtüş-mektedir.…”
Section: Discussionunclassified
“…It is a vicious circle. Currently, a major proportion of elderly in the western world is overmedicated [3]. In sharp contrast with this diseases of civilization are virtually absent in contemporary hunter-gatherer societies [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that polypharmacy is more common in man at abroad studies. 6,7,8 In our country Cakmur et al found polypharmacy is more common in female and this situation is associated with female participants are two folds of male participants, female lifespan is longer than male's and female patients come doctor's office more often. 3,6,9 In some other studies found polypharmacy is more common in male.…”
Section: 24mentioning
confidence: 99%